The 6xABRE Synthetic Promoter Enables the Spatiotemporal Analysis of ABA-Mediated Transcriptional Regulation. Issue 4 (8th June 2018) - Wu, Rui; Duan, Lina; Pruneda-Paz, José L.; Oh, Dong-ha; Pound, Michael; Kay, Steve; Dinneny, José R.
Abstract : Spatiotemporal analysis of ABA-signaling in plants reveals the dynamics of osmotic stress signaling in roots and identifies novel regulators of ABA-dependent transcriptional programs. Abstract: The water stress-associated hormone abscisic acid (ABA) acts through a well-defined signal transduction cascade to mediate downstream transcriptional events important for acclimation to stress. Although ABA signaling is known to function in specific tissues to regulate root growth, little is understood regarding the spatial pattern of ABA-mediated transcriptional regulation. Here, we describe the construction and evaluation of an ABSCISIC ACID RESPONSIVE ELEMENT (ABRE)-based synthetic promoter reporter that reveals the transcriptional response of tissues to different levels of exogenous ABA and stresses. Genome-scale yeast one-hybrid screens complemented these approaches and revealed how promoter sequence and architecture affect the recruitment of diverse transcription factors (TFs) to the ABRE. Our analysis also revealed ABA-independent activity of the ABRE-reporter under nonstress conditions, with expression being enriched at the quiescent center and stem cell niche. We show that the WUSCHEL RELATED HOMEOBOX5 and NAC DOMAIN PROTEIN13 TFs regulate QC/SCN expression of the ABRE reporter, which highlights the convergence of developmental and DNA-damage signaling pathways onto this cis-element in the absence of water stress. This work establishes a tool to study the spatial pattern of ABA-mediated transcriptional regulation and a repertoire of TF-ABRE interactions that contribute to the developmental and environmental control of gene expression in roots.